PENGARUH BEBAN KENDARAAN TERHADAP UMUR DESAIN PERKERASAN (STUDI KASUS JALAN NASIONAL LAMBARO – BATAS PIDIE PROVINSI ACEH) - Denny Firdaus; Muhammad Isya; Sofyan M. Saleh (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Better capabilities of a vehicle (higher speeds, larger payloads) allows freight operators to perform "transport efficiency" (carrying goods as much as possible in one way that will provide benefits). This problem affects the cumulative equivalent standard axle (CESA) plan, which will experience a shift (Plans of CESA are reached before the service Period of the construction ends). The study is located on the eastern route of Aceh Province, especially on Lambaro-Pidie border. The purpose of this research was to know the relation of vehicle load with time, how to design pavement age and residual CESA value, in the service lifespan (time) of construction (10 years). The data used in this study was secondary data obtained from relevant agencies. The method used in this research was descriptive by doing comparison analysis to the relationship that happened. The data analysis and simulation were conducted in 3 scenarios, where Scenario 1 refers to the design data, Scenario 2 refers to the actual average daily traffic and the standard axle, and Scenario 3 refers to the actual LHR and actual axle load (Weigh in measurement results Motion-WIM). From the results of this study, it is known to simulate vehicle loads with time, Scenario 1 is y = 1,0794x - 2171,3, Scenario 2 y = 0,4935x2 - 1987,9x + 2E+06, and Scenario 3 y = 0,8605x2 - 3466,3x + 3E+06. The result of simulation lifespan of pavement design and CESA value, it is known that pavement design lifespan has decreased on average by 3.5 years, and CESA residual value is 42,138,92 thousand ESA.